1990
DOI: 10.1111/j.2044-8295.1990.tb02368.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of photic stimulation and private self‐consciousness on the complexity of visual imagination imagery

Abstract: Three levels of photic stimulation (6, 10, 18 Hz) were employed to induce visual imagination imagery in 40 female undergraduates, half of whom had been selected because they had an habitual interest in their own internal states and half because they had no such interest (high and low on a Private Self-conscious (PSC) scale). It was predicted, and found, that more complex images would be reported (1) under the averaged 6 and 10 Hz condition than under the 18 Hz condition, (2) under the 6 than under the 10 Hz co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…There are pure imaginationimagery processes at the far right of the continuum (Figure 3). Even though imaginationimagery might appear dynamic and real, the self-creation of content or events unrelated to actual experiences is involved and this is, apparently, novel for users (Richardson and McAndrew, 1990). When it is translated into the context of digital media usage, imaginationimagery is able to let users: picture themselves as better selves, reflecting life aspirations; live out an ideal and non life-related identity; or 'be' in a virtual and fiction-derived territory (Molesworth, 2009).…”
Section: A Critical View Of the Imagery Domain And Its Extension To Dmentioning
confidence: 99%
“…There are pure imaginationimagery processes at the far right of the continuum (Figure 3). Even though imaginationimagery might appear dynamic and real, the self-creation of content or events unrelated to actual experiences is involved and this is, apparently, novel for users (Richardson and McAndrew, 1990). When it is translated into the context of digital media usage, imaginationimagery is able to let users: picture themselves as better selves, reflecting life aspirations; live out an ideal and non life-related identity; or 'be' in a virtual and fiction-derived territory (Molesworth, 2009).…”
Section: A Critical View Of the Imagery Domain And Its Extension To Dmentioning
confidence: 99%
“…AVE affects electroencephalographic (EEG) output (Toman,1940;Walter, 1956;Barlow, 1960;Inouye, Sumitsuji, & Matsumoto, 1979;Kinney, McKay, Mensch, & Luria, 1972;Nogawa, Katayama, Tabata, Ohshio, & Kawahara, 1976;Lesser, Luders, Klem, & Dinner, 1986;Frederick, Lubar, Rasey, Brim, & Blackburn, 1999). It is purported to alter perception and consciousness (Glicksohn,1986;Richardson & McAndrew, 1990;Freedman & Marks, 1965). AVE has been used to improve grade-point average in college students (Budzynski, Jordy, Budzynski, Tang, & Claypoole, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, research with versions of the private self-consciousness measure first constructed by Fenigstein, Scheier, and Buss (1975) has produced similar evidence (e.g., Nasby, 1989) that those who know themselves best (i.e., are most self-aware) make more accurate estimates of their actual behavior than those who know themselves least. Again, when Richardson and McAndrew (1990) used a shortened version of this scale that emphasized internal state awareness (rather than mere self-reflectiveness), they found that more complex imagination images were reported (under conditions of photic stimulation) by those who were most aware of their internal states.…”
Section: Methods Of Investigationmentioning
confidence: 96%